Analisis Kontrastif Bentuk dan Makna Kata Majemuk Bahasa Jepang dan Bahasa Indonesia - Made Henra Dwikarmawan Sudipa; I Wayan Wahyu Cipta Widiastika; Gusti Ayu Made Yuni Mahadewi; Ni Luh Yunda Anindyana (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study analyzes the similarities and differences between Japanese and Indonesian compound words, with particular attention to their structural patterns and semantic characteristics. The data were collected from official news websites in Japan and Indonesia, including Asahi Shinbun and Kompas, through observation and note-taking techniques. The collected data were analyzed through the distributional method, and the contrastive analysis was conducted based on morphological theories proposed by Chaer (2015), Katamba (2018), and Kageyama (2016). The findings reveal that ten Japanese and Indonesian compound words share equivalent meanings. From a structural perspective, both languages exhibit various types of compound formations, including noun, adjective, and verb compounds. A notable structural difference is that Japanese compound words may undergo a phonological process known as rendaku. From a semantic perspective, compound words in both languages may be categorized as endocentric and exocentric. However, some compounds do not share the same idiomatic meanings, even though they are constructed from identical lexemes in each language.